2017
DOI: 10.18632/oncotarget.17256
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin regulates macrophage activation by inhibiting NLRP3 inflammasome-p38 MAPK-NFκB pathways in autophagy- and p62-dependent manners

Abstract: Excessive and prolonged activation of macrophages underlies many inflammatory and autoimmune diseases. To regulate activation and maintain homeostasis, macrophages have multiple intrinsic mechanisms, one of which is modulation through autophagy. Here we demonstrate that autophagy induction by rapamycin suppressed the production of IL-1β and IL-18 in lipopolysaccharide- and adenosine triphosphate-activated macrophages at the post-transcriptional level by eliminating mitochondrial ROS (mtROS) and pro-IL1β in a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
107
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(113 citation statements)
references
References 69 publications
6
107
0
Order By: Relevance
“…It accumulates when autophagy is deficient. Previous studies demonstrate that rapamycin treatment inceased p62 levels in different cell lines and may have enhanced effects on autophagy . In agreement with these previous reports our results demonstrate an increase in p62 with rapamycin treatment and this increase in p62 levels dropped significantly with Burkholderia infection in vitro compared to only Burkholderia infection.…”
Section: Discussionsupporting
confidence: 93%
“…It accumulates when autophagy is deficient. Previous studies demonstrate that rapamycin treatment inceased p62 levels in different cell lines and may have enhanced effects on autophagy . In agreement with these previous reports our results demonstrate an increase in p62 with rapamycin treatment and this increase in p62 levels dropped significantly with Burkholderia infection in vitro compared to only Burkholderia infection.…”
Section: Discussionsupporting
confidence: 93%
“…There is increasing evidence that autophagy has a regulatory function in inflammation as well as having an antiinflammatory effect [31,32]. However some reports found that autophagy might …”
Section: Exos From Mir-30d-5p-overexpressing Adscs Are More Effectivementioning
confidence: 99%
“…In addition, recent evidence suggests that NLRP3 is a convergent point of antiaging interventions. NLRP3 inflammasome is inhibited by rapamycin, metformin, or resveratrol through regulation of mTOR, AMPK, and Sirt1 [130,131]. Interestingly, nutrients status is shown to modulate the NLRP3 inflammasome in human and mouse.…”
Section: Nlrp3 Inflammasomementioning
confidence: 99%